National collegiate athletic association division I assistant coaches` understanding and use of mental performance and mental health services - Eckenrod, M. R.; Hill, H.; Thompson, M.; Neelis, L. A.; Donahue, P. T. (The Sport Psychologist, 2023)
Assistant coaches play an important role in National Collegiate Athletic Association (NCAA) athletic departments and spend substantial amounts of time working with student-athletes, yet no research to date has examined their knowledge of mental performance and mental health services. Therefore, the purpose of this study was to learn about NCAA Division I assistant coaches` understanding and use of mental performance and mental health services. Thirteen assistant coaches employed at universities with at least one mental performance consultant and one licensed mental health provider were interviewed. Thematic analysis procedures were used, and five themes were constructed: (a) day-to-day responsibilities of the assistant coach, (b) needing both mental performance and mental health services, (c) factors influencing understanding of mental performance and mental health services, (d) factors impacting student-athlete utilization of mental performance and mental health services, and (e) confusion between mental performance and mental health services.